2D MXene Nanomaterials: Synthesis, Mechanism, and Multifunctional Applications in Microwave Absorption. Issue 10 (19th August 2022) - Guan, Xiaomeng; Yang, Zhihong; Zhou, Ming; Yang, Le; Peymanfar, Reza; Aslibeiki, Bagher; Ji, Guangbin
Abstract : MXene nanomaterials stand out among 2D nanomaterials and have been extensively studied by researchers because of their unique layered structure, chemical diversity, and outstanding chemical and physical properties. In recent years, MXene materials have rapidly opened the market for electromagnetic interference shielding technology due to their excellent electromagnetic wave absorption (EMA) capability. However, so far, compared with the development of electromagnetic (EM) shielding technology, there is still much room for development in the construction of MXenes and the application of electromagnetic wave absorption. Herein, the construction strategies, electromagnetic wave conversion mechanism, and applications of MXenes materials are reviewed. Through meticulous material design and an interdisciplinary approach, 2D MXene materials are expected to become one of the smart tunable wave absorbers, and their application scenarios will also become broader. Abstract : This review mainly introduces the construction route of 2D MXene and their composites. In addition, the effects of surface groups on the microstructure and electromagnetic properties are also discussed. The latest progress in multifunctional applications is elaborated. Finally, research priorities are proposed on how to overcome future challenges and opportunities in this field.